Catalytic microreactor with immobilised silver nanocluster for organic pollutant removal from water. (2016) - Habibi, Mehdi; Barkallah, Amine; Ognier, Stéphanie; Mostafavi-Amjad, Jafar; Khalesifard, Hamid R.M.; Tatoulian, Michael; Shahidzadeh, Noushine; Bonn, Daniel
The use of microchannels for catalytic reactions represents a considerable experimental opportunity, because of the high surface area to volume ratio these devices typically have. However, incorporating catalysts into microfluidic devices has proven technically challenging. We report the development of a new type of microfluidic device that has a catalytically active metal surface with a large active area built into one of the walls that constitute the microchannel. We test the catalytical activity on an important chemical reaction for drinking water purification: the catalytic ozonation of a typical organic pollutant that is otherwise difficult to remove from the water. pCBA was chosen as model pollutant since it is known to have slow reaction rates with molecular ozone and hence to pose problems in water purification. We find that the catalytic microreactor increases the overall reaction rate by a factor 350 compared to the bulk reaction, owing to both the catalytic activity and the confinement, and is thus highly efficient even for very short residence times.